2008
DOI: 10.1186/1471-230x-8-13
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of biochemical dysfunction of the liver in Atayal Aboriginal community of Taiwan: Is betel nut chewing a risk factor?

Abstract: Background: We address the independent and interactive roles of habitual betel quid chewing and other known risk factors for biochemical dysfunction and cirrhosis of the liver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 35 publications
(36 reference statements)
0
19
0
Order By: Relevance
“…It is known that persistent hepatic inflammation is a hallmark of habitual BQ chewing (Sarma et al, 1992;Gupta and Warnakulasuriya, 2002;Lin et al, 2008) and/or chronic HBV/HCV infection (Bouchard and Navas-Martin, 2011;El-Serag, 2012). Our results indicated that habitual BQ chewing do increase risk for HCC (Table 2) and hepatic fibrosis regardless of chronic hepatitis B or hepatitis C (Table 4 and Table 5).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…It is known that persistent hepatic inflammation is a hallmark of habitual BQ chewing (Sarma et al, 1992;Gupta and Warnakulasuriya, 2002;Lin et al, 2008) and/or chronic HBV/HCV infection (Bouchard and Navas-Martin, 2011;El-Serag, 2012). Our results indicated that habitual BQ chewing do increase risk for HCC (Table 2) and hepatic fibrosis regardless of chronic hepatitis B or hepatitis C (Table 4 and Table 5).…”
Section: Discussionmentioning
confidence: 54%
“…Persistent hepatic inflammation is a hallmark of habitual BQ chewing (Sarma et al, 1992;Lin et al, 2008;Angadi and Rao, 2011) and/or chronic HBV/HCV infection (Bouchard and Navas-Martin, 2011;El-Serag, 2012). Hepatic fibrosis, or cirrhosis, is a common end-stage condition of many chronic liver diseases (Bouchard and Navas-Martin, 2011;Luedde and Schwabe, 2011;El-Serag, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the Atayal tribe is Taiwan's second largest Indigenous group after the Amis. The Taiwan Atayal people have preserved their own languages (Huang 2008;Tsai and Wu 2012), customs (Chang et al 2008), diets (Lin et al 2008), and social organizations (Tang and Tang 2010).…”
Section: Research On Taiwanese Indigenous Peoplesmentioning
confidence: 99%
“…A large community study in Taiwan from 2003 to 2004 illustrated that the prevalence of elevated ALT in an adult population was 11.4%, and non-alcoholic fatty liver disease (NAFLD) seemed to be the most common cause of elevated ALT [9]. Moreover, there were 16.5% adults with abnormal ALT levels in an Atayal indigenous community [10]. Previous cross-sectional studies have reported a positive association between serum ALT level and MetS [11,12].…”
Section: Introductionmentioning
confidence: 99%